Assessing Public Perception Of Government Communication Strategies During The 2019 Microfinance And Bank Shutdowns In Ghana - Armah, Charity Naa Dedei (UniMAC, 2025)
This study interrogates public perception of government communication strategies during the 2019 microfinance and bank shutdowns in Accra, Ghana, a crisis that necessitated major financial sector reforms but profoundly eroded public trust. Employing a concurrent triangulation mixed-methods design, the research integrated quantitative surveys of 100 residents with in-depth qualitative interviews of 20 affected individuals in selected communities. The findings, structured around four research objectives, reveal a severe communication breakdown. Residents experienced the crisis as a period of deep personal devastation and financial anxiety, with their trust in the financial system fundamentally shattered. The government’s multi-channel communication strategy, while utilising both traditional and digital media, was critically ineffective; messages were consistently criticised as delayed, overly technical, inaccessible due to language barriers, and lacking in empathy. Consequently, public satisfaction with official communication was extremely low, as strategies failed to provide clarity, reassurance, or actionable guidance. The study identified key challenges, including contradictory messaging, the rapid spread of misinformation, and the exclusion of vulnerable, low-literacy populations. Based directly on these empirical insights, the study recommends a fundamental overhaul of crisis communication, proposing a unified, apolitical, and empathetic framework that prioritises plain language in local dialects, leverages trusted community channels, and fosters proactive, two-way public engagement. This research contributes to crisis communication theory within the Global South context and offers evidence-based policy recommendations for rebuilding trust and ensuring effective public discourse during future financial reforms.
Keywords: government communication strategies; microfinance; financial sector reforms; Ghana